The magic hat shop - Wimmer, Sonja (Cuento De Luz, 2016)
"One day, a hat shop mysteriously appears in the main square of a little town. The townspeople are surprised by this new arrival, but then something happens that nobody expects: the first customers put on their hats, and make an amazing discovery. A delightful tale about magic hats and bonnets, but above all about the importance about being yourself and the hidden treasures we carry within us."--Back cover.